Synthesis of multiarm star block copolymer based on host-guest inclusion complexation - Yiğit, Neşe Çakır; Hızal, Gürkan; Tunca, Ümit (İdris Karagöz, 2022)
Supramolecular multiarm star block copolymer ((CD-PEG)p-(Ada-PS)n-polyDVB) was prepared by host-guest interaction of ?-cyclodextrin ( ?-CD) end functionalized polyethylene glycol (?-CD-PEG) and adamantane peripherally functionalized multiarm star polymer ((Ada-PS)n-polyDVB). The ?-CD-PEG was synthesized by copper-catalyzed azide/alkyne cycloaddition reaction (CuAAC) of alkyne functional PEG with mono azide functional ?-CD (?-CD-N3). Adamantane functional polystyrene (Ada-PS) was prepared by atom transfer radical polymerization (ATRP) of styrene (St) and was allowed to react with divinyl benzene (DVB) as a linking agent giving (Ada-PS)n-polyDVB multiarm star polymer. The structures of ?-CD-PEG and (Ada-PS)n-polyDVB multiarm star formation were determined by 1H NMR and GPC. 2D ROESY NMR and DLS analysis of (CD-PEG)p-(Ada-PS)n-polyDVB were carried out to validate the formation of the inclusion complex. The evidence of increased molecular weights and size distributions supported the supramolecular multiarm star block copolymer formation.
Keywords: Polymer Science and Technologies; Polimer Bilimi ve Teknolojileri